Verification of serialising instructions for security against transient execution attacks - Kushal K. Ponugoti; Sudarshan K. Srinivasan; Nimish Mathure (IET Computers & Digital Techniques)
Abstract Transient execution attacks such as Spectre and Meltdown exploit speculative execution in modern microprocessors to leak information via cache side‐channels. Software solutions to defend against many transient execution attacks employ the lfence serialising instruction, which does not allow instructions that come after the lfence to execute out‐of‐order with respect to instructions that come before the lfence. However, errors and Trojans in the hardware implementation of lfence can be exploited to compromise the software mitigations that use lfence. The aforementioned security gap has not been identified and addressed previously. The authors provide a formal method solution that addresses the verification of lfence hardware implementation. The authors also show how hardware Trojans can be designed to circumvent lfence and demonstrate that their verification approach will flag such Trojans as well. The authors have demonstrated the efficacy of our approach using RSD, which is an open source RISC‐V based superscalar out‐of‐order processor.